Introduction: Labor Migration in Ukraine and the Post-Soviet Space - Bolat, Zhanna (Dve domovini, 2024)
This themed section of Dve domovini / Two Homelands illuminates significant contemporary migration and labor migration trends in the post-Soviet space. Ukraine has experienced substantial emigration in recent decades, spurred by economic uncertainties and the conflict in eastern Ukraine since 2014. Labor migration is a major phenomenon, partly facilitated by Ukraine’s visa-free access to the EU, which provides more opportunities for temporary work abroad (Kortukova, 2021). However, large-scale emigration of working-age Ukrainians poses risks of “brain drain” and other socioeconomic impacts (Spanger & Andersen, 2023). Kazakhstan has also seen substantial emigration and immigration, mainly to and from neighboring countries like Russia and Uzbekistan, for economic reasons. Newly restrictive residence permit regulations in Kazakhstan may alter these longstanding migration dynamics within the region. Japan is gradually easing some of its previously strict immigration policies to fill acute labor shortages in the construction, home healthcare, and agriculture sectors. However, tensions remain around the integration of migrants into Japanese society. Public attitudes do not always align with government efforts to accept more foreign workers (Liu, 2023). Meanwhile, many Tajiks engage in temporary cyclical labor migration to Kazakhstan, working in trade sectors like markets or transportation. Their collective family-based migrant enterprises demonstrate resilience in the face of challenging conditions, though restrictive and unpredictable migration policies in Kazakhstan create precarity.